PERANCANGAN LAYANAN KTP ELEKTRONIK DI DESA/KELURAHAN MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING - , Albertus Harys Yunanto, Dr. Ir. Eko Nugroho, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Public services are expected by the public is easy, simple, smooth, fast and precise service. One of public service form is a service of demography in the village. Demography service in the village can reduce the number of queues at the district level service applicant so the applicant can be served more quickly. Demography services at the village can also reduce the hidden cost that appears to get the service. Electronic ID card is one of the Government policy in the field of demography. By default place-based electronic ID card service for Citizen Identification Number of the National is in the district. Electronic ID card service in the district could cause problems if the number of applicants each day cannot be served in full. By lowering the electronic ID card service points in village can divide the number of electronic ID card applicants to multiple points of service so that all the electronic ID card applicants can be served in full. By using the methodology of Enterprise Architecture Planning (EAP) is designed enterprise architecture of an electronic ID card services in villages, according to the government program, to realize a service population that is easy, cheap and fast. EAP defines the data architecture, applications and technologies needed to support the organization's business processes. Architecture that is built up consisting of data architecture, applications, technology and implementation plan.